PEMBENTUKAN LEMBAGA LUMBUNG DESA DI GROBOGAN PADA AWAL ABAD XX (History Department, Semarang State University and Historian Society of Indonesia, 2010)
Grobogan was regency directly ruled by Dutch Colonial government. At that time this regency was identified as a poor region. The poverty was mainly caused by unstable food supply. The aim of this research is to describe village economy institution in forming Village Barn as a tool for creating stability in food supply. The research focused on Grobogan regency, Central Java in the early of the 20th century. This research used historical sources especially the secondary ones in the form of monograph and other printed sources. The research found out that before establishing Village Barn Institution, the condition of Grobogan people was under instability of food supply. But then, after Village barn was formed, the condition of instability in food supply ended. In conclusion, the Forming of Village Barn influenced the food supply stability. So, it is strongly suggested that Village Barn can be revitalized again nowadays. Key word: village barn, food supply, poverty, stability, instability, institution Grobogan adalah Kabupaten yang secara langsung diatur oleh pemerintah Kolonial Belanda. Pada waktu itu Kabupaten ini diidentifikasi sebagai satu daerah lemah. Kemiskinan sebagian besar disebabkan oleh persediaan makanan yang tidak stabil. Penelitian ini bertujuan mendeskripsikan institusi ekonomi desa beurpa pembentukan Lumbung Desa sebagai satu alat untuk menjaga ketahanan pangan. Penelitian yang difokuskan di Grobogan, Jawa Tengah pada awal 20 abad. Penelitian ini menggunakan sumber historis dan sumber sekunder beurpa monograf dan sumber tercetak yang lain. Hasil penelitian menunjukkan sebelum mendirikan Institusi Lumbung Desa, kondisi orang-orang Grobogan di bawah ketidakstabilan dari barang persediaan makanan. Akan tetapi, setelah Lumbung Desa dibentuk, kondisi ketidakstabilan di barang persediaan makanan berakhir. Kesimpulannya, Pembentukan Lumbung Desa mepengaruhi kemantapan barang persediaan makanan. Sehingga, betul-betul disarankan bahwa Lumbung Desa dapat direvitalisasi kembali pada saat ini. Kata kunci: Lumbung desa, persediaan makanan, kemiskinan, kemantapan, ketidakstabilan, institusi